Cover Picture: Understanding the (De)Sodiation Mechanisms in Na‐Based Batteries through Operando X‐Ray Methods (Batteries & Supercaps 7/2021). Issue 7 (2nd June 2021) - Brennhagen, Anders; Cavallo, Carmen; Wragg, David S.; Sottmann, Jonas; Koposov, Alexey Y.; Fjellvåg, Helmer
Abstract : The Front Cover shows a team of scientists performing operando studies on a sodium battery, as it were a real patient in a hospital. Operando X‐ray methodologies deliver valuable information about the structural, atomistic, and morphological changes while the battery is actually in its working state. More information can be found in the Review by C. Cavallo and co‐workers .